Lenguaje oral y lectura inicial en alumnos del primer grado de primaria de dos instituciones educativas del Callao - Delgado Tipacti, Ruth Margarita (2012)
The research was aimed to determine the relationship between oral language and early reading. The study of correlational descriptive type was conducted with a sample of 100 students (52 males and 48 females) age 6, the first grade two state educational institutions of Callao. Tests were applied: Oral Language Assessment Palm Square and Fernandez (2008) and Reading Level 1 of De La Cruz (1979), adapted versions in Lima. The results indicated significant relationship of oral language with the initial reading taking into account the overall scores. The results of the semantic and syntactic subtest oral language, reading correlated with baseline were significant, but not auditory discrimination and phonological correlated. Auditory stimuli, visual understanding significantly correlated with oral language, visual discrimination not. Subjects achieved average in oral language, and high and middle in initial reading.